Radiation-Induced Optical Coherence Tomography Angiography Retinal Alterations in Patients With Nasopharyngeal Carcinoma - Li, Zijing; Zhan, Zongyi; Xiao, Jianhui; Lan, Yuqing (Frontiers in Medicine, 2021)
AIM: To investigate the early neuro-vascular alterations of the retina in radiation encephalopathy (RE) patients with normal-ranged visual acuity after radiotherapy for nasopharyngeal carcinoma. METHODS: Fifty-five RE patients with and 54 healthy age-matched subjects were enrolled in this retrospective study. The best corrected visual acuity (LogMAR) of the included eye should not be more than 0. The vessel density and thickness of different locations in the retina were acquired automatically using optical coherence tomography angiography (OCTA). The data was then compared between the RE and the control. The location included the whole retina, the ganglion cell complex (GCC), the deep vascular plexus (DVP) and choroid in the macular area as well as inside disc and peripapillary area in the optic nerve head (ONH). The risk factors in OCTA retinal impairments were analyzed. The relationships between mean deviation (MD) and pattern standard deviation (PSD) in the visual field (VF) and the OCTA parameters were also analyzed in the RE. RESULTS: The vessel density of the GCC was significantly reduced in RE patients compared to controls (p=0.018) and the reductions were mainly shown in the parafoveal (p=0.049) and perifoveal field (p=0.006). The thickness of GCC were correspondingly reduced (whole image GCC mean thickness: p=0.044; parafoveal thickness: p=0.038; perifoveal thickness: p=0.038). In addition, the sub-foveal choroidal thickness (p=0.039) was also reduced in RE patients. The vessel density of the GCC and DVP had a significant positive correlation with high density lipoprotein cholesterol (HDL-C) and apolipoprotein A1 (ApoA1) and had a significant negative correlation with age. Vessel density of the GCC also had a significant negative correlation with apolipoprotein B (ApoB). In VF, MD had a significant positive correlation with the vessel density inside disc while PSD showed a significant negative correlation with the vessel density inside disc and the average GCC thickness, respectively. CONCLUSION: With the aid of OCTA, we found that neuro-vascular alterations of the retina may exist in RE patients with normal-ranged visual acuity. Herein, we suggest the implementation of OCTA to assist ophthalmologists in the early detection and consistent monitoring of radiation-related eye diseases to avoid delayed diagnosis.